Clip[4]arene: synthesis, rigid acyclic C-shaped structure, and redox-controlled host–guest complexation. Issue 13 (28th March 2018) - Zhao, Run; Jie, Kecheng; Zhou, Yujuan; Li, Errui; Liu, Jiyong; Huang, Feihe
Graphical abstract: Highlights: A novel, easily available and rigid acyclic C-shaped host–clip[4]arene. The stoichiometry of paraquat with clip[4]arene is 1:1 in acetone but 2:1 in the solid state. The complexation between clip[4]arene and paraquat is redox-controlled. Abstract: Here we report the synthesis of a novel, easily available and rigid acyclic C-shaped host−−clip[4]arene. It has the ability to bind electron-poor pyridinum salts in solution. A bipyridinum salt, paraquat, is found to have a 1:1 complexation stoichiometry in acetone but a 2:1 complexation stoichiometry in the solid state with clip[4]arene. Unlike traditional [2]pseudorotaxanes with structures of linear guest molecules threaded into macrocyclic hosts, the complex of clip[4]arene and paraquat is rather a [2]pseudoclipaxane where a linear molecule is threaded through a rigid acyclic C-shaped molecule. Furthermore, the complexation between clip[4]arene and paraquat is redox-controlled and can be reversibly regulated through the sequential addition of Zn powder and exposure to air.